MINERALOGICAL AND CHEMICAL CHARACTERISATION ON STIBNITE FROM ALLCHAR LOCALITY, NORTH MACEDONIA (Natural Resources and Technology, 2022)
Crystalline stibnite occurrences in the Republic of Macedonia to several antimony deposits such as Allchar, Lojane and Krstov dol. The best stibnite cristyals can be found in the central parts of the Allchar mine. Crystals of stibnite are thick to thin elongated prisms with vertical striations, lead gray colour and high metallic lustres. Stibnite also occurs in columnar, granular, blamnded and compact habits. Cleavage is perfect on {010} and imperfect on {100},{110}. The density determined by pycnometer is 4.62 g/cm3. Hardnes is 2. The concentration of the oxides is: Sb:70,912-71,155%, S:27,166-28,166%. Also were detected the following trace elements: Tl, Cr, Ba, Se, V and W. The unit cell parameters obtained using the main reflection lines of X-ray diffraction are: a = 11.24 Å, b = 3.84 Å, c = 11.34 Å, V = 490.43 Å3,Z: 4.
Keywords: stibnite, Allchar, SEM-EDS, ICP-MS, XRD